2013
DOI: 10.1002/jmri.24110
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional hemodynamics in intracranial aneurysms: influence of size and morphology

Abstract: Purpose To employ 4D-flow MRI for the comprehensive in-vivo analysis of hemodynamics and its relationship to size and morphology of different intracranial aneurysms (IA). We hypothesize that different IA groups, defined by size and morphology, exhibit different velocity fields, wall shear stress and vorticity. Materials and Methods 4D-flow MRI (spatial resolution=0.99–1.8×0.78–1.46×1.2–1.4mm3, temporal resolution=44–48ms) was performed in 19 IAs (18 patients, age=55.4 ± 13.8 years) with saccular (n=16) and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 49 publications
1
77
0
Order By: Relevance
“…[37][38][39] Moreover, previous studies confirmed the feasibility of depicting the aneurysmal inflow. 18,20,23,26,27 Consequently, 4D flow MR imaging is the criterion standard for the identification of the inflow zone of cerebral aneurysms. According to others, 11,13,40 the inflow zone of lateral-projection aneurysms was located on the distal neck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39] Moreover, previous studies confirmed the feasibility of depicting the aneurysmal inflow. 18,20,23,26,27 Consequently, 4D flow MR imaging is the criterion standard for the identification of the inflow zone of cerebral aneurysms. According to others, 11,13,40 the inflow zone of lateral-projection aneurysms was located on the distal neck.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, 4D flow MR imaging based on time-resolved 3D cine phase-contrast MR imaging techniques was used to evaluate the hemodynamics of cerebral aneurysms. [18][19][20][21][22][23][24][25][26][27] However, 4D flow MR imaging requires additional time for data acquisition, and TC 3D MRA may be a convenient alternative to 4D flow MR imaging for identifying the aneurysmal inflow zone.…”
Section: -15mentioning
confidence: 99%
“…Aneurysms are pathologic dilations of the vessel wall, and their flow characteristics have been extensively investigated as mechanically and biologically related with the initiation, growth, and eventual rupture of aneurysms (Cebral et al 2011;Geers et al 2011;Schnell et al 2014;Gopalakrishnan et al 2014;Arzani et al 2016).…”
Section: Cerebral Arteries With Aneurysmsmentioning
confidence: 99%
“…The increasing number of studies applying the MRI-based WSS estimation in-vivo [23,[34][35][36][37][38][39][40][41][42][43] prompt detailed investigations of the accuracy of MRI-based WSS estimation. Estimates of WSS from 4D flow data in an intracranial aneurysms showed large discrepancies compared to subject-specific CFD simulations [36].…”
Section: Mri-based Wall Shear Stress Estimationmentioning
confidence: 99%
“…The use of 4D flow MRI has increased the understanding of normal and abnormal blood flow and has proven valuable in various clinical applications [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Ample evidence indicates that WSS is involved in the pathogenesis of atherosclerosis and aneurysms [28][29][30][31][32][33], and an increasing number of studies apply MRI-based WSS estimation invivo [23,[34][35][36][37][38][39][40][41][42][43]. However, many cardiovascular applications of 4D flow MRI require large volumetric coverage resulting in scan times of about 20-40 minutes, which may be prohibitive in many cases.…”
Section: Introductionmentioning
confidence: 99%